Purification, characterization and partial amino acid sequences of thermo-alkali-stable and mercury ion-tolerant xylanase from Thermomyces dupontii KKU–CLD–E2–3 - Seemakram, Wasan; Boonrung, Santhaya; Aimi, Tadanori; Ekprasert, Jindarat; Lumyong, Saisamorn; Boonlue, Sophon (Scientific reports, 2020)
We investigated the properties of the low molecular weight thermo-alkali-stable and mercury ion-tolerant xylanase production from Thermomyces dupontii KKU-CLD-E2-3. The xylanase was purified to homogeneity by ammonium sulfate, Sephadex G–100 and DEAE–cellulose column chromatography which resulted 27.92-fold purification specific activity of 56.19 U/mg protein and a recovery yield of 2.01%. The purified xylanase showed a molecular weight of 25 kDa by SDS–PAGE and the partial peptide sequence showed maximum sequence homology to the endo-1,4-β-xylanase. The optimum temperature and pH for its activity were 80 °C and pH 9.0, respectively. Furthermore, the purified xylanase can maintain more than 75% of the original activity in pH range of 7.0–10.0 after incubation at 4 °C for 24 h, and can still maintain more than 70% of original activity after incubating at 70 °C for 90 min. Our purified xylanase was activated by Cu 2+ and Hg 2+ up to 277% and 235% of initial activity, respectively but inhibited by Co 2+ , Ag + and SDS at a concentration of 5 mM. The K m and V ma x values of beechwood xylan were 3.38 mg/mL and 625 µmol/min/mg, respectively. Furthermore, our xylanase had activity specifically to xylan-containing substrates and hydrolyzed beechwood xylan, and the end products mainly were xylotetraose and xylobiose. The results suggested that our purified xylanase has potential to use for pulp bleaching in the pulp and paper industry.